Implementation of Marriage Guardianship in Indonesian Positive Law: An Analysis of Wali Hakim and Wakalah Wali - Illian Hikma; Muliadi; Ferdian; Firmansyah; Nanta Septia (VRISPRAAK : International Journal of Law, 2026)
Marriage in Islamic law is constructed as a very strong covenant (mīthāqan ghalīẓan) whose validity depends on fulfilling the pillars (rukun) and conditions (syarat), one of which is the presence of a marriage guardian (wali nikah). Under Indonesian positive law, guardianship has experienced significant regulatory dynamics following the issuance of the Minister of Religious Affairs Regulation (PMA) Number 30 of 2024 concerning Marriage Registration. This normative-prescriptive legal research aims to analyze the structuring and hierarchy of lineage guardians (wali nasab) post-enactment of PMA Number 30 of 2024, examine the judicial-administrative mechanism of the sovereign guardian (wali hakim) in resolving emergencies, and assess the legal status of wakālah al-walī (taukil wali) as an instrument of social elasticity for modern society. The approaches used are the conceptual approach, statute approach, and case approach. The results indicate: First, PMA Number 30 of 2024 tightens the verification process of lineage guardians through the absolute requirement of birth certificates, the removal of masks/veils during examination for visual identification, and the signing of an Absolute Responsibility Statement (SPTJM). Second, the institution of wali hakim is positioned as a bridge for legal emergencies executed selectively and limitatively, where wali ‘aḍal disputes must go through a Religious Court decision before being executed by the Head of KUA. Third, the institution of wakālah al-walī (both through pasrah wali and taukil bil kitabah) functions as a manifestation of secondary benefit (maṣlaḥah ḥājiyyah) that provides efficient socio-geographical administrative solutions for the community, while preventing the spread of unregistered marriages (nikah siri) that harm women's civil rights. This study concludes that the positive legal system in Indonesia harmoniously synergizes state administrative certainty with the theological demands of Islamic law.